ANALISIS TINGKAT KESEHATAN PT BANK PEMBANGUNAN DAERAH SULAWESI UTARA GORONTALO DENGAN METODE RGEC PERIODE 2016-2020 - Tatyana Tatyana; Ni Made Artini; Adezia Zefanya Michela (Institut Teknologi dan Bisnis Swadharma, 2022)
Bank business activities require an assessment of the healthy of the bank so that public confidence in a bank can increase. Therefore, the purpose of this study was to determine the health level of PT. Regional Development Bank of North Sulawesi Gorontalo for the 2016-2020 period. This writing using the RGEC method to examine events that had occurred and to find out the factors that could cause these events to occur. The results of research and data analysis show the risk profile of the SulutGo bank using two credit risk factor indicators, namely using the NPL ratio and the LDR. Liquidity risk ratio during 2016-2020 in a healthy condition. Bank SulutGo in 2016-2020 obtained composite 2 which shows the implementation of good corporate governance although in 2017 it slightly decreased to a composite that reflects good corporate governance. The profitability (income) of the SulutGo bank using indicators, namely ROA and BOPO during 2016-2020 is in a very healthy condition, indicating that SulutGo bank has succeeded in carrying out its operations effectively; The results of the assessment of Bank SulutGo's capital during the current year are in a very healthy condition, namely 2016-2020, far above the minimum standard set by Bank Indonesia, which is 8%. This shows that so far, SulutGo bank has been able to manage capital well